Cross-sectional hospital-based study on the seroprevalence of hepatitis B virus markers among healthcare workers, NWR, Cameroon. Issue 7 (1st July 2021) - W Akazong, Etheline; Tume, Christopher; Ayong, Lawrence; Njouom, Richard; Kenmoe, Sebastien; Njankouo, Ripa; Kuiate, Jules-Roger
Abstract : Background: Hepatitis B virus (HBV) infection is a major public health issue worldwide, with about 257 million people reported to be chronic carriers by the WHO fact sheet updated in 2018. HBV can be contracted via direct contact with infected body fluid and infection is almost always asymptomatic. Although healthcare workers (HCWs) are at high risk of HBV infection, little is known about the prevalence of the various HBV markers among HCWs in Cameroon. The present study was taken to evaluate the prevalence of different HBV serological markers among HCWs in the North-West Region of Cameroon. Methods: This cross-sectional hospital-based study was carried out between April and September 2017 during which 395 HCWs were recruited. The serum of the HCWs were tested for the presence of HBV core antibody, hepatitis B surface antibody, hepatitis B e antibody and hepatitis B surface antigen using Monalisa ELISA kits produced by BIO-RAD laboratories. Data were analysed using SPSS V.20.0. Results: Among the 395 participants, 270 (68.4%) of them were females, 187 (47.3%) had been exposed to HBV, 145 (36.7%) had resolved the infection, 42 (10.6%) were current HBV carriers, 10 (2.5%) were infective, 36 (9.1%) were vaccinated and 172 (43.5%) were still susceptible. Exposure to HBV, past infection and susceptibility were significantly associated with age while the rate of vaccination was significantly associated with the job of the HCW in the health facilities. Conclusion: The prevalence of HBV exposure and infection among HCWs obtained in this study was high while the level of vaccination in this at-risk population was low. Adequate steps should be taken to sensitise this population on HBV and the vaccination procedure.